Adventures in Speech : Rhetoric and Narration in Boccaccio's Decameron - Forni, Pier Massimo (The Middle Ages Series, 2016)
Selected by Choice magazine as an Outstanding Academic Book for 1996 The Decameron is a narrative account of a situation in which narration takes place-a collection of one hundred stories set within a larger story. As a group of young men and women fleeing the plague trade stories to pass the time of crisis, storytelling occurs in a social context that allows for comment upon the tales by the tellers themselves, in a setting that elicits one story in return for another. In his close and original analysis, Pier Massimo Forni uses the notion of rhetoric as a guiding principle for a critical assessment of the Decameron. He explores the discursive tools with which the narrators connect the contents of their stories to their audience's environment, and goes on to argue that the book is significantly marked by Boccaccio's habit of exploring the narrative potential of rhetorical forms.